Clinical presentations, electrophysiologic features, and long-term follow-up in Lambert–Eaton myasthenic syndrome: a series of six patients - Alhammad, Reem M.; Alshamlan, Yafa; Alneseyan, Ruwa; Al-Harbi, Talal M.; Alhijab, Ali; Alanazy, Mohammed H. (Frontiers in Neurology, 2024)
BackgroundLambert–Eaton myasthenic syndrome (LEMS) is an autoimmune disorder of the presynaptic neuromuscular junction associated with antibody mediated dysfunction of voltage-gated calcium channels (VGCCs). LEMS can exist as a paraneoplastic syndrome, paraneoplastic-LEMS (P-LEMS), when associated with tumors, most commonly, small cell lung carcinoma (SCLC) or as a non-paraneoplastic condition (NP-LEMS) when no malignancies are detected.MethodsA retrospective chart review was conducted in 3 tertiary hospitals in Saudi Arabia for patients diagnosed with LEMS between January 2010 and January 2020. Patients meeting all the following criteria were included: (1) weakness or fatigability of one or more extremity or oculo-bulbar muscles, (2) 60% or higher increment of compound muscle action potential (CMAP) amplitudes immediately following isometric exercise, and (3) positive serum P/Q type VGCC antibodies. Clinical, laboratory, and electrophysiologic features, as well as radiologic imaging modalities performed for tumor screening were reviewed.ResultsThe study included six patients diagnosed with LEMS, split evenly between P-LEMS and NP-LEMS. Fatigability, particularly in the lower extremities, and dyspnea on exertion were commonly reported symptoms. Low CMAP amplitudes were more frequently seen in NP-LEMS as compared to P-LEMS when recorded from both abductor pollicis brevis and abductor digiti minimi muscles. An incremental response above 60% in post activation CMAPs was detected at similar rates following variable durations of isometric exercise (10, 15, and 20 s). Tumor types detected in 3 patients with P-LEMS are SCLC, breast carcinoma, colon adenocarcinoma, and prostate acinar adenocarcinoma. Triple malignancy was detected in one patient.ConclusionThis is the first study to describe clinical and electrophysiologic features of LEMS in an Arab ethnic cohort. Early recognition of LEMS has a significant impact on prognosis, especially given the aggressive nature of associated cancers such as SCLC.